Molecular turn in Yersinia pestis pathogenesis: implications of the gppA frameshift for bacterial survival in human macrophage - Hongyan Chen; Shiyang Cao; Yazhou Zhou; Tong Wang; Yang Jiao; Yafang Tan; Yarong Wu; Yifan Ren; Yajun Song; Jing-Ren Zhang; Zongmin Du; Ruifu Yang (Emerging Microbes and Infections)
Yersinia pestis, the etiological agent of the devastating plague, has caused three pandemics in human history. While known for its fatality, it has long been intriguing that biovar microtus strains are highly attenuated to humans. The survival and replication within macrophages are critical in the early stages of the Y. pestis lifestyle within warm-blooded hosts. Here, we demonstrate that a frameshift truncation of gppA, a gene encoding the phosphohydrolase GppA that responsible for the conversion of stringent response alarmone pppGpp to ppGpp, significantly promotes Y. pestis to survive inside human macrophages. This frameshift mutation of gppA is present in all the evolutionary branches formed by the modern Y. pestis strains responsible for the plague pandemics, while the relative ancient microtus strains express a functional GppA showing high activity in catalyzing pppGpp to ppGpp conversion. This adaptive evolution potentially explains why microtus Y. pestis strains exhibit attenuated virulence in humans in contrast to the lethal pathogenicity of non-microtus strains. Transcriptome analysis suggests that the disturbed balance of the ratio of ppGpp to pppGpp caused by GppA inactivation results in an upregulation of genes involved in the synthesis of branched-chain amino acids, which are essential for bacterial growth. This enhanced survival ability within macrophages could be a key factor for the virulence of Y. pestis towards humans. Our work sheds light on the molecular mechanisms behind Y. pestis host-specific pathogenicity, offering significant implications for enhancing our ability to predict and counteract the emergence of new infectious diseases.